IMPROVING STUDENTS’ UNDERSTANDING OF INDONESIAN CULTURE THROUGH ENGLISH LEARNING BASED LOCAL CULTURE CONTEXT - Seftika Seftika; Miftahul Janah; Wuri Syaputri (Universitas Lancang Kuning, 2017)
Learning English as a foreign language usually related to learning culture of the target language. However, for maintainning local culture and fostering Indonesian unity, the researchers try to use local cultural material in teaching English. This study aims to know students’ understanding toward Indonesian culture, and to know their English speaking improvement after inserting local culture knowledge in Learning. The culture focused on this study are lampungnese, javanese, sundanese, padangnese, and palembangnese ethnic since these ethnics are dominant in students’ environtment. This study used quasy-experimental design. The participants were the second semester students of English Department of STKIP Muhammadiyah Pringsewu. In collecting the data the researchers employed speaking test for measuring students’ speaking skill and open-ended quetionnaire for knowing students’ understanding on local culture. The result shows that transmitting local cultural knowledge through English learning makes students to be more familiar and understand the local culture. Moreover their awareness of cultural diversity are improved due to the fact that they more appreciate on the differences that cause an effective communication in social life. Consequently, students’ speaking skill are improved through practicing English as means for transferring local culture knowledge.